ANALISIS DAMPAK BANTUAN PROGRAM PENANGGULANGAN KEMISKINAN TERHADAP KONDISI EKONOMI MASYARAKAT MISKIN DI DESA ANESE KECAMATAN ANDOOLO BARAT KABUPATEN KONAWE SELATAN - Andriyansa Andriyansa; Yohanes Boni; La Tondi (JEP (Jurnal Ekonomi Pembangunan), 2022)
This study aims to analyze the impact of poverty alleviation program assistance on the community's economy. The results of the study show that the poverty alleviation program has not improved the economy of the poor. This can be seen from the poverty rate which is still increasing in 2020 by 11.28%, while the achievement target in the 2020 Konawe Selatan Regency RPJMD is 10.70%. This means that the poverty alleviation program implemented by South Konawe Regency has not reduced the poverty rate. The Family Hope Program (PKH) rating is 59.63%, meaning that the implementation of PKH has not gone well. The assessment of the Healthy Indonesia Card Program (KIS) was 79.65%, meaning that the implementation of the KIS was considered good, this was supported by a decrease in the number of sick people and the achievement of fulfilling health facilities obtained by the community. The assessment of the Smart Indonesia Card Program (KIP) was 72.98%, meaning that the provision of KIP has been good in helping the poor, this can be seen from the increase in the number of school children and the decrease in the dropout rate.